1991
DOI: 10.1557/proc-254-3
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Kinetics and Practice of Low Angle Ion Beam Thinning

Abstract: The thinning technique is based on a simple geometrical model, describing the changes in the surface topography during ion beam etching. A high ion beam density makes jt possible that a thinning with an incidence angle of 0.5–7° ( measured from the sample surface) can take place within a reasonable time. Our method is applicable to a wide range of materials and to XTEM preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…In order to study the tool-chip interface, a technique which can produce high quality electron transparent specimens of the highly localized cutting zone is required. Traditional cross-sectional TEM sample preparation techniques, e.g., mechanical polishing followed by ion-milling of coatings as described in [4], are not well suited. There are a few studies published where the authors have used a refined traditional preparation technique [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In order to study the tool-chip interface, a technique which can produce high quality electron transparent specimens of the highly localized cutting zone is required. Traditional cross-sectional TEM sample preparation techniques, e.g., mechanical polishing followed by ion-milling of coatings as described in [4], are not well suited. There are a few studies published where the authors have used a refined traditional preparation technique [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Kovac et al [18] also reported ripple formation on bulk (50 nm thick) C sample at 1 keV Ar + ion bombardment for various parameters, but they also showed the disappearance of ripples if specimen rotation had been used. It is also well established that the usage of grazing angle of incidence for ion bombardment also reduces the morphology development [19]. Moreover, it should also be mentioned that the ion bombardment induced morphology change is proportional to the removed layer thickness [19,20].…”
Section: Discussion and Simulation Of The Depth Profilesmentioning
confidence: 99%
“…It is also well established that the usage of grazing angle of incidence for ion bombardment also reduces the morphology development [19]. Moreover, it should also be mentioned that the ion bombardment induced morphology change is proportional to the removed layer thickness [19,20]. Since the layer thickness to be removed in the present case is in the range of 1-2 nm, and we apply specimen rotation during sputtering and grazing angle of incidence we do not expect such morphology development which could impair measurement of the layer thickness.…”
Section: Discussion and Simulation Of The Depth Profilesmentioning
confidence: 99%
“…If no special precautions are taken, preferential ion milling effects are often observed for heterogeneous samples due to the different thinning rates of materials (Barna, 1984). Surfaces can be smoothed at small angles of incidence; however, resputtering can also occur (Barna, 1992). The beam invariably disrupts the surface as it penetrates, and defects can be generated in the surface .…”
Section: Ion Millingmentioning
confidence: 99%